Profile of linguistic and cognitive deficits in persons with a semantic variant of a primary progressive aphasia - Jerkić, Lana; Pavlović, Dragan; Vuković, Mile; Todorović, Jelena; Zelić, Mirna (Medicinski časopis, 2021)
Primary progressive aphasia (PPA) includes a group of neurodegenerative disorders that are characterized by progressive deterioration of language functions, while other cognitive functions, at least at the onset of the disease, are relatively spared. There are three basic subtypes of PPA: the nonfluent progressive aphasia (nvPPA), the semantic variant of a primary progressive aphasia (svPPA), and the logopenic progressive aphasia (lvPPA). The semantic variant of a PPA can also be found in the literature under the term of semantic dementia. It is clinically manifested by progressive deterioration of semantic knowledge, fluent aphasia, impaired naming and comprehension, prosopagnosia and surface dyslexia and dysgraphia (in languages ​​with irregular orthography). As the disease progresses, other cognitive changes can be observed. The main cause of the disorder is progressive bilateral atrophy of the anterior temporal lobes, which is more manifested in the left hemisphere. The literature is modest in terms of the use of specific treatment methods in the rehabilitation of these patients. Since speech and language disorders are the most conspicuous symptom, at least at the beginning of the disease, the role of speech therapists in the assessment and restitution of speech-language and communication skills is also indisputable.
Keywords: primary progressive aphasia, semantic dementia, semantic variant of primary progressive aphasia, language disorders